Mental Health and Labour Supply – Evidence from Mexico's Ongoing Violent Conflicts - Maren M. Michaelsen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
In Mexico, conflicts between drug-trafficking organisations result in a high number of deaths and immense suffering among both victims and non-victims every year. Little scientific research exists which identifies and quantifies the monetary and nonmonetary consequences of ongoing violent conflicts on individuals. Using the Mexican Family Life Survey for 2002 and 2005, the causal effect of mental health (symptoms of depression / anxiety) on the extensive and intensive margin of labour supply for working-aged men and women is estimated. Measures of the ongoing drug-related violent conflicts both at the macro level using intentional homicide rates by region, and at the micro level indicated by the presence of armed groups in the neighbourhood, serve as instruments for mental health. The results show a signifi cant adverse impact of the conflicts on anxiety for men and women. Based on IV-Tobit model results, a worse mental health state decreases individual labour supply strongly and significantly for men. The findings demonstrate that Mexico's population not only suffers from the violent conflicts between drug-trafficking organisations by anxiety or even depression but also indirectly from less household income through less work which in turn has consequences for Mexico's social development and economic growth. – – In Mexico beherrschen seit vielen Jahren gewalttätige Konflikte zwischen Drogenkartellen den Alltag. Dies führt zu großem Leid bei direkten und indirekten Opfern. Es existiert allerdings nur eine geringe Anzahl an wissenschaftlichen Arbeiten, die die monetären und nicht-monetären Konsequenzen identifizieren und quantifizieren. Die vorliegende Arbeit benutzt Daten des Mexican Family Life Survey für die Jahre 2002 und 2005 und identifiziert den kausalen Effekt von mentaler Gesundheit auf das individuelle Arbeitsangebot. Dabei wird sowohl die extensive Marge als auch die intensive Marge betrachtet. Maßzahlen der gewalttätigen Konflikte auf Mikro- und Makroebene, nämlich Mordstatistiken und die Anwesenheit von bewaffneten Gruppen in der Nachbarschaft der befragten Personen, dienen als Instrumente für mentale Gesundheit. Die Ergebnisse weisen einen signifikanten negativen Effekt der Konflikte auf Angstzustände von Männern und Frauen auf. Auf Basis von IV-Tobit Modell-Ergebnissen zeigt sich, dass ein schlechterer mentaler Gesundheitszustand das individuelle Arbeitsangebot von Männern stark senkt. Die Ergebnisse zeigen, dass Mexikos Bevölkerung nicht nur durch die Konflikte im Sinne von schlechterer mentaler Gesundheit leidet, sondern auch indirekt durch geringeres Einkommen, das aufgrund von weniger Arbeit erzielt wird. Dies könnte langfristig negative Auswirkungen auf die soziale Entwicklung und wirtschaftliches Wachstum in Mexiko haben.
Keywords: J22; I19; O12; D74; 330; mental health; labour supply; violent conflict; Mexico